Comparative metabolomics of two saline-alkali tolerant plants Suaeda glauca and Puccinellia tenuiflora based on GC-MS platform. Issue 3 (1st February 2021) - Lu, Xueyan; Chen, Qi; Cui, Xiaoyang; Abozeid, Ann; Liu, Yang; Liu, Jia; Tang, Zhonghua
Abstract: Suaeda glauca and Puccinellia tenuiflora are two important saline-alkali tolerant plants that can improve the soil properties. For exploring the different tolerance mechanisms between them, GC-MS-based metabolomics was used to comprehensively evaluate the primary metabolites differences, a total of 51 different metabolites were present in different quantities. The identified compounds were mainly 11 sugars, 7 amino acids, 5 alcohols and 18 organic acids; they play an important role in responding to the saline-alkali stress and distinguish between S. glauca and P. tenuiflora . All identified metabolites classes showed similar trend to largely accumulate in P. tenuiflora roots and S. glauca shoots, this reveals that the two plants used different physiological strategies to cope with saline-alkali stress. Abstract :